“FISH BOX PERLTIER COOLER” FISH COLLING BOX EQUIPPED WITH PELTIER ELECTRIC COOLER (PEC) - Achmat Soleh; Rio Antoni; Alfian Dwi Cahyo; Muhammad Rifandiansyah; Yusuf Mochammad Saputra; Agung Prijo Budijono (AIBPM Publisher, 2018)
The Purpose The purpose of this study is to provide solutions of SMEs D.SadewaKenjeran Beach related to traditional storage of marine fish products that is still using ice cubes as a cooler in the box of fishes storage. Method The method used by using Peltier Electric Cooler (PEC) in the box of fishes storage to produce stable temperature. The PEC box control system is equipped with Arduino and programmed with CX programmer. It is designed to accommodate 15kg of fish per process. Result The expected result is to improve the stability of the cooling process (below 100C), the growth of bacteria will be slower so that the product can last longer. So the productivity of SMEs can be increased 2 times with the capacity of box 15 kg of fishes. The Finding The findings of this study are the usage of 15 kg PEC box fish with Arduino CX Programmer temperature control system as a solution of storage problems of marine fish products. Keywords :Peltier Electric Cooler (PEC), SMEs, Box, Fish